TEOLOGI DAN MEDIA SOSIAL: (Studi Analisis Konten Akidah di WhatsApp Ditinjau dari Perspektif Teologi Islam) - Joni Harnedi; Fachrur Rizha (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2020)
Social media is a means of delivering public information. In its use, social media can be used to spread Islamic da'wah. However, social media can also become a hotbed for spreading hoax news from certain circles by using the Al-Qur'an and Hadith as references. From a number of social media, this research focuses on the use of WhatsApp social media. This study uses a qualitative approach with content analysis methods from personal messages to researchers or through groups or communities that are followed through WhatsApp messages. The results showed that the disseminated content model included messages that were disseminated and linked religious threats to physical and health threats. Though these threats are certainly not found in religions that originate from the Al-Quran or the Prophet's Hadith. A number of messages that are conveyed also have da'wah values, such as the prohibition of dying from prayer, but when it is related to replies and threats that have no evidence in the Al-Qur'an and Hadith, these messages are no longer in accordance with Islamic teachings.